Hepatic Microenvironment Affects Oval Cell Localization in Albumin-Urokinase-Type Plasminogen Activator Transgenic Mice - Braun, Kristin M.; Thompson, Anne W.; Sandgren, Eric P. (The American journal of pathology, 2003)
Mice carrying an albumin-urokinase type plasminogen activator transgene (AL-uPA) develop liver disease secondary to uPA expression in hepatocytes. Transgene-expressing parenchyma is replaced gradually by clones of cells that have deleted transgene DNA and therefore are not subject to uPA-mediated damage. Diseased liver displays several abnormalities, including hepatocyte vacuolation and changes in nonparenchymal tissue. The latter includes increases in laminin protein within parenchyma and the appearance of cytokeratin 19-positive bile ductule-like cells (oval cells) both in portal regions and extending into the hepatic parenchyma. In this study, we subjected AL-uPA mice to two-thirds partial hepatectomy to identify the response of these livers to additional growth stimulation. We observed several changes in hepatic morphology. First, the oval cells increased in number and often formed ductules in the parenchyma. Second, this cellular change was accompanied by a further increase in laminin associated with single or clusters of oval cells. Third, desmin-positive Ito cells increased in number and maintained close association with oval cells. Fourth, these changes were localized precisely to uPA-expressing areas of liver. Regenerating clones of uPA-deficient cells appeared to be unaffected both by stromal and cellular alterations. Thus, additional growth stimulation of diseased uPA-expressing liver induces an oval cell-like response, as observed in other models of severe hepatic injury, but the localization of this response seems to be highly regulated by the hepatic microenvironment.